Voltage balancing in the system of power supply of high-speed rail transport - Juraeva Kamila Komilovna; Rustemova Aynura Rustemovna (Research Parks Publishers, 2020)
The article deals with the issues of voltage balancing in power supply systems for high-speed electric transport. Considered the possibility of using balancing devices for traction networks.